Bioenergetics and Trophic Impacts of Invasive Indo-Pacific Lionfish - Cerino, David S.; NC DOCKS at East Carolina University (2011)
Indo-Pacific lionfish Pterois volitans and Pterois miles are non-native marine fish with established populations in the western North Atlantic Ocean and Caribbean Sea. Rapid population growth threatens native fish communities and they are considered invasive species. A bioenergetics model was developed for lionfish and applied to populations inhabiting the western North Atlantic Ocean to model the potential impact of these predators on native reef ecosystems. Model parameters were derived by laboratory evaluation of consumption and respiration rates from 14 to 32Â° C and fish size ranging from 19 to 400 g. The model was calibrated with laboratory growth and consumption data and model performance was analyzed to evaluate the parameters most sensitive to error. The optimal temperature for lionfish consumption is 29.8Â° C. Energy allocated to gamete production reduces female lionfish growth rate compared to males and limits maximum body size. Based on the environmental conditions and observed growth daily consumption estimates of 393 lionfish [dot in center of line] ha-1 could remove up to 2.186 kg prey [dot in center of line] d-1 during the summer in the Bahamas. The corroborated model is a useful tool for examining the influence of temperature on predation rates and exploring the interaction between lionfish and prey.